Controle de Meloidogyne incognita raça 1 com óleo essencial de Lippia alba - Marino, Regina Helena; Gomes, Luiz Antônio Augusto; de Oliveira Cruz, Elizangela Mércia; Silva, Anderson de Carvalho; Bianchini, Flávio Gabriel; Meneses, Thaís Nascimento; Santos, Hercules Rosário; Blank, Arie Fitzgerald (Scientia Plena, 2012)